Respiratory muscle strength in asthmatic children - Marcelino, Alessandra Maria Farias Cavalcante; da Cunha, Daniele Andrade; da Cunha, Renata Andrade; da Silva, Hilton Justino (International Archives of Otorhinolaryngology, 2012)
Introduction: Changes in the respiratory system of asthmatics are also due to the mechanical disadvantage caused by the increased airway resistance.Objective: The study aims to evaluate the respiratory muscle strength and nutritional status of asthmatic children.Method: This is a prospective descriptive and transversal study with 50 children aged 7 to 12 years, who were placed into 2 groups, asthmatic and non-asthmatic. Respiratory muscle strength was evaluated on the basis of maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP). The nutritional status was evaluated by measuring the anthropometric data, including height, weight, and body mass index (BMI). The findings were subjected to analysis of variance, chi-square, and Student's t test, and p-values < 0.05 was considered statistically significant.Results: In our comparisons, we observed statistically significantly lower values for age, weight, and height in asthmatic patients: 8.52 ± 1.49 years, 30.62 ± 7.66 kg, and 129.85 ± 10.24 cm, respectively, vs. non-asthmatic children(9.79 ± 1.51 years, 39.92 ± 16.57 kg, and 139.04 ± 11.62 cm, respectively). There was no significant increase in MIP and MEP between the groups: MIP was -84.96 ± 27.52 cmH2O for the asthmatic group and -88.56 ± 26.50 cmH2O for the non-asthmatic group, and MEP was 64.48 ± 19.23 cmH2O for asthmatic children and +66.72 ± 16.56 cmH2O for non-asthmatics.Conclusion: There was no statistically significant difference between groups, but we observed that MIP and MEP were slightly higher in the non-asthmatic group than in the asthmatic group.
Keywords: asthma; muscle strength; respiratory muscles